Kajian Soal-soal dalam Buku Teks Matematika Kelas V Berdasarkan Frameworks PISA - Ningsih, Dewina Cahya; Susanta, Agus (Jurnal Didaktika Pendidikan Dasar, 2022)
Questions, one of the content text books components, play an essential role in a learning activity. The analysis of textbook aims to determine the quality of the questions used by schools in improving Mathematical literacy skill as an essential ability students should acquire in the Mathematics learning process. This study aimed to analyze the characteristics of the questions in the Mathematic text book based on PISA frameworks. The PISA frameworks consisted of content, context, process, and cognitive level. This research used qualitative descriptive method. The subject of this research were 115 competency test questions in the Mathematic text book. The results showed that the number of questions using the PISA framework was 65 questions (56.5%). The content aspect is dominated by space and form 35 questions (53.8%). The context aspect that is often used is the scientific context with 34 questions (52.3%). The process aspect is dominated by aspects of formulating 52 questions (80%). The cognitive level of  questions reaches cognitive level 3 applying with a distribution of cognitive level 1 remembering (12 questions or 18.5%), cognitive level 2 understanding (49 questions or 75.4%), and cognitive level 3 applying (4 questions or 6,1%).